2023
DOI: 10.2166/wh.2023.258
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acanthamoeba spp. in groundwater sources in a rural area in the Philippines

Abstract: Research on free-living amoebae (FLA) and its public health implication as an etiologic agent of parasitic infection in humans has recently gained traction in the Philippines. This study aimed to identify potential FLAs in collected groundwater samples from Masinloc, Zambales, Philippines. Fifty-four (54) water samples were collected in 250-mL sterile polyethylene containers by purposive sampling from selected groundwater sources in six (6) barangays of Masinloc. The samples were vacuum filtered through a 1.2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…drinking (tap and bottled) and recreational (swimming pools, spas and beaches), well water and groundwater ( de Lacerda and Lira, 2021 ; Masangkay et al, 2022 ). Reports performing genotyping on water samples have indicated that genotypes are present which are known to cause human disease including the dominant T4 genotype ( Putaporntip et al, 2021 ; Padua et al, 2023 ). In addition to T4, we report the T3 genotype from individuals presenting with AK, which is similar to previous reports from three continents supporting its association with this disease ( Diehl et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…drinking (tap and bottled) and recreational (swimming pools, spas and beaches), well water and groundwater ( de Lacerda and Lira, 2021 ; Masangkay et al, 2022 ). Reports performing genotyping on water samples have indicated that genotypes are present which are known to cause human disease including the dominant T4 genotype ( Putaporntip et al, 2021 ; Padua et al, 2023 ). In addition to T4, we report the T3 genotype from individuals presenting with AK, which is similar to previous reports from three continents supporting its association with this disease ( Diehl et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…It also has a worldwide distribution, and it has been detected in a variety of niches, including natural freshwater sources (e.g. hot springs, groundwater, and spring water), air conditioning units, and even public swimming pools in some countries [25 ▪ ,29,32–35]. Furthermore, Acanthamoeba has been detected in drinking water systems in many countries, including 51% of households sampled in one US study [36,37].…”
Section: Environmental Nichementioning
confidence: 99%